Climate change trauma and collective dissociation: Unraveling the impact on mental health and advocating for collective action - Deborah Oluwaseun Shomuyiwa; Don-Eliseo Lucero-Prisno (Cambridge Prisms: Global Mental Health)
The climate change crisis is a complex global challenge that has far- reaching implications for public health and well-being. Rising temperatures and more frequent extreme weather events are impacting physical health, mental well-being, and ecological balance. Vulnerable communities are disproportionately affected, especially in terms of food security. Furthermore, climate-related disasters have profound and lasting effects on mental health, leading to trauma responses and dissociation as coping mechanisms. This perspective delves into the concept of collective dissociation, a subconscious defense mechanism that hinders effective action in the face of the overwhelming climate crisis. Understanding and characterizing this phenomenon is essential to promote meaningful climate action. To combat collective dissociation and facilitate effective collective action, several strategies are proposed. Responsible information management for advocacy, local moral support, strategic policy development, and research on climate trauma processing are highlighted as vital approaches. By addressing the mental health implications of climate change, raising awareness, and prioritizing resilience and cooperation, societies can transcend collective dissociation and work together towards a more sustainable future for both the planet and its inhabitants. This call to action underscores the need for comprehensive and guided measures to safeguard planetary and population health in the face of this pressing crisis.